1948
DOI: 10.5962/bhl.title.7443
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to medical mycology, by George M. Lewis and Mary E. Hopper.

Abstract: gous diseases encountered were concerned, no variation from the findings in civilian life was noted. However, on the basis of possibility of spread, some uncommon diseases of limited distribution, such as Paracoccidioides, mycetoma and tinea imbricata, received considerable attention. To date no reports have shown any spread of these or of other unusual fungous diseases in this country. It is apparent that in medical mycology much important work remains to be done. CHAPTER IIClassification of Fungi FUNGI are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1948
1948
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The core idea of self-organization is a characteristic that between multiple individuals which follow a set of simple rules, it can independently, asynchronously interact with each other, and reveal response or adaptive approach [10]. It is a method to achieve macroscopically objectives of the system by individual microcosmic behavior.…”
Section: Service Self-organizationmentioning
confidence: 99%
“…The core idea of self-organization is a characteristic that between multiple individuals which follow a set of simple rules, it can independently, asynchronously interact with each other, and reveal response or adaptive approach [10]. It is a method to achieve macroscopically objectives of the system by individual microcosmic behavior.…”
Section: Service Self-organizationmentioning
confidence: 99%
“…Thus Muskatblit (1941), who described six instances, was only able to find another 36 recorded by previous workers. However, Lewis and Hopper (1943) described 23 more cases, and remarked that such infections were probably commoner than had been thought in the past. This was confirmed by Hopkins et al (1947), who found them in 5-7% of 1700 cases of tinea pedis.…”
Section: Mixed Infectionsmentioning
confidence: 98%
“…Carex vallicola has a wide range in the Great Plains, Rocky Mountains and Great Basin, but it is poorly known in Montana. Studies in Utah suggest that the species has undergone a decline due to its high palatability and sensitivity to grazing (Lewis 1958). Distribution and population trends m…”
Section: F Management Considerationsmentioning
confidence: 99%